Comparative Analysis Of Rice Productivity: Csa Technology With Conventional Technology - Prasetyo, Kunandar; Utami, Dewanti Risa; Kinding, Dwi Putriana Nuramanah; Handayani, Rr. Tri; Bayumurti, Seno (Universitas Djuanda, 2025)
Rice productivity plays a crucial role in global food security, particularly in Indonesia. However, climate change has become one of the biggest challenges faced by various sectors of life, especially agricultural commodities. Climate Smart Agriculture (CSA) integrates climate change adaptation and mitigation as well as increasing agricultural productivity through environmentally friendly practices. This study aims to examine the comparison of rice farming productivity between CSA and conventional systems in Kemangkon District, Purbalingga, with a sample size of 48 rice farmers using the CSA system and 48 conventional rice farmers, analyzed using the Independent T-Test method. The results of this study indicate that there are differences in rice productivity between farmers who have used the CSA system compared to conventional systems. The average rice productivity of farmers using CSA technology was 71,07 kw/ha, while rice productivity for farmers using conventional technology was 62,42 kw/ha. Therefore, various comprehensive policies are needed to increase the adoption of CSA technology at the farmer level, such as developing comprehensive training programs on CSA technology and establishing demonstration plots (demplot).